The association between refrigerator use and carbon footprint of household food waste: empirical evidence from China - Zhang, Li; Ye, Linxiang; Qian, Long; Han, Jingwei; Zuo, Xiuping; Li, Yuting (Frontiers in Sustainable Food Systems, 2025)
Food waste in household settings contributes 66% of the global carbon footprint of food waste. Reducing food waste at the household level is essential for global environmental sustainability. Based on the China Health and Nutrition Survey (CHNS) and the China Food Life Cycle Assessment Database (CFLCAD), this paper explores the resource and environmental impacts of food waste from the perspective of the use of refrigeration equipment as a refrigerator in Chinese households, and based on life cycle theory. The primary findings are that (1) Refrigerator use significantly reduces the carbon footprint of household food waste. (2) Dietary knowledge plays a moderating role in the food waste carbon footprint effect of refrigerator use. (3) Heterogeneity analyses show that the effect of refrigerator use on household food waste carbon footprint varies according to the gender and education level of the household head, household per capita income level and urban-rural type. This paper provides evidence that the popularization of refrigerators reduces the carbon footprint of household food waste in China, which may have implications for other countries.